Recuperación de la memoria histórica de la parroquia Quimiag a través del registro del Patrimonio Cultural Inmaterial. - Lara Usca, Carmen Noemí (2019)
The present investigation proposes: The Recovery of the Historical Memory of the Parish of Quimiag through the registry of the Intangible Cultural Heritage; it consists of 3 chapters, the first corresponds to the epistemological conceptualization of cultural heritage, where the aspects of intangible cultural heritage are analyzed, in the second chapter an ethnographic study of the historical-cultural memory of the Quimiag parish is analyzed, corresponding to the pre-active stage, where part of the history and its immaterial cultural heritage of the locality could be known through the unstructured interviews that were carried out with the residents, through the interviews the registration was made in the INPC files to help conservation Some of the manifestations that still remain in force in the parish and others that have been lost over time due to various social factors remain within the historical memory of the parish, in the third chapter with the active stage of the procedure supported by the formative ethnographic method, the analysis of the With a diagnostic stage where we report the low participation of residents during the collection of information, in the active stage we propose a school project aimed at the students of the 3 EGB Bernardo Castillo school, so that through the application children can Recognize the traditions that your locality has.